Self-concept as a measure of success in the military environment - Besener, Paul Robert (Rhodes University, Faculty of Education, Department of Education, 1987)
This piece of research is an attempt to evaluate the relationship between military 'success' and the psychological preparedness of recruits in terms of their self-concepts and locus of control orientations. The new recruit is forced to adapt to the military environment which will, in turn, attempt to change him into an effective soldier. It was noticed by the researcher, who was involved in military training at the time, that a number of recruits, even some with seemingly limited potential, coped well, while others who seemed to have the ability failed to cope adequately. Recruits completed questionnaires which provided the researcher with biographical data and background information. In addition, the Bledsoe Self-Concept Scale and the Nowicki and Strickland Locus of Control Scale were used in order to determine their self-concepts and locus of control orientations respectively, prior to the beginning of national service. Detailed unstructured interviews were also conducted with a sample of military personnel, to provide another basis for gathering data and for clarifying some of the issues involved. Briefly, the chief conclusion of this researcher is that a significant majority of 'successful' recruits in the military environment have a positive self-concept and an internal locus of control. On the basis of the above finding, it is suggested that there is a need to guide pupils about certain aspects of military life before they begin their National Service. There would seem to be a need for this guidance to be incorporated into the school curriculum, together with such practical aspects as cadets, shooting, etc. There is a shortage of this kind of research on the military situation in South Africa, and it is suggested that numerous issues in this field need to be researched for the benefit of future conscripts and the military alike.
Keywords: Self-perception; Control; Recruits; Soldiers; Military; National service -- South Africa; Pupils; Learners; Guidance; School curriculum